Comparative Study with a Unique Arrangement to Tap Piezoelectric Output to Realize a Self Poled PVDF Based Nanocomposite for Energy Harvesting Applications. Issue 9 (27th April 2017) - Pusty, Manojit; Sharma, Alfa; Sinha, Lichchhavi; Chaudhary, Anjali; Shirage, Parasharam
Abstract: In this research paper we present a comparative study on the enhanced piezoelectric performance between Carbon Nanotubes (CNT)/PVDF nanocomposite as well as Iron‐Reduced Graphene Oxide (Fe‐RGO)/PVDF nanocomposite. The enhanced performance is realized by a unique device structure, in which the bottom electrode is physically not in contact with the piezoelectric film until external excitation is applied. FTIR characterization shows the enhancement of polar crystallization phases due to electrostatic interactions in PVDF by the addition of CNT and Fe‐RGO. Raman Spectroscopy indicates the formation of good quality Fe‐RGO nanosheets and also shows high crystalline quality of CNTs. Raman Spectroscopy identifies the interaction between CNTs and Fe‐RGO nanosheets with the polymer that supports the piezoelectric current generation mechanism. Conductivity measurements show that addition of CNT and Fe‐RGO in PVDF increases the conductivity of the nanocomposite films. The CNT/PVDF and Fe‐RGO/PVDF piezoelectric energy harvesting device produced an open circuit output voltage of 2.5 V and 1.2 V respectively. A short circuit rectified current of nearly 700 nA and 300 nA was detected by the CNT/PVDF and Fe‐RGO/PVDF based piezoelectric energy harvesting device. Abstract : In this work we have designed a novel device to harvest mechanical energy from human finger tappings to generate electrical energy from nanomaterial/polymer nanocomposite. The piezoelectric performance of the polymer enhances with the incorporation of nanomaterials by ensuring detection of measurable electrical current and voltage. Such nanotechnology mediated lightweight and conveyable mechanical energy harvesting device made by piezoelectric polymers may lead to provide maintenance free energy solutions of future to charge portable electronic devices.